THE ROLE OF TRADITIONAL SONGS IN OUR SOCIETY - A.A.Eshimuratova (Western European Studies, 2025)
After gaining independence, each nation, with a deep look at its history, paid attention to its nationality. The performance of "yor-yor" at a bride's wedding has been revived thanks to the fact that it is one of the national traditions that has become deeply ingrained in our souls. The article discusses the role of traditional songs in the life of our people, their unique characteristics, and the signs of their traditions and customs.
Keywords: discusses; customs; people